PEMILIHAN KODE DALAM MASYARAKAT DWIBAHASA: MASYARAKAT JAWA DI DAERAH JATIBENING BEKASI - HANIFA, NINIP (JURNAL PENDIDIKAN BAHASA DAN SASTRA, 2011)
The study of language in relation with social factors is very fascinating. The migration of inhabitants of one city into another causes the interaction between visitors and local population within the community, that results language contact.The research aims at describing the language variety, code switching and code mixing of Javanese speech community in Jatibening area.This research uses fields study based on qualitative approach. The result shows that the variety of codes are the type of code switching and code mixing. The codes which are found in the Javanese speech community in Jatibening are Indonesian Language (BI), Javanese language (BJ), other local languages (BL), and foreign language (BA).Â  The code switching in Javanese speech community results four varieties, i.e. Indonesian language, Javanese language, foreign language, and other local language. Based on the situational code-switching, the language change happens because of (1) the change of setting, (2) the appearance of other participants, (3) the change of topic. On the other hand, based on metaphorical code-switching, the language change takes place because the participants want to emphasize on something. Code mixing happens because of (1) the limitation of the code usage and (2) the use of more popular terms.Keywords: language variety, code switching, code mixing